Perspektif Pemangku Kepentingan di Kabupaten Penukal Abab Lematang Ilir Tentang Pengelolaan Sampah Rumah Tangga - Dian Novriadhy; Ani Kurnia; Sri Maryani; Achmad Ubaidillah; Hendrixon Hendrixon (Seminar Nasional Lahan Suboptimal, 2018)
Novriadhy et al, 2019. Stakeholder Perspective in Penukal Abab Lematang Ilir District Concerning Household Waste Management. pp. 347-353. Households are the biggest waste producers. Therefore, household waste management must be done carefully and efficiently - especially for the New Autonomous Region - so as not to consume all resources that needed for development. This research was carried out in PALI District with the aim to identify the needs in waste management based on cross-sectoral stakeholder perspectives. Research informants came from local government units, nongovernment organizations, waste management practitioners, and small business groups. Data collected through FGD, observation and literature search. The data is processed with a qualitative approach and interpreted by the input-process-output method. The results showed three key factors needed for waste management i.e. the existence of the compost market, the availability of environmental cadres, and an environmental management working group that could synergize programs/activities from various stakeholders whereas the supporting factors were the funding method, regulatory enforcement, and adequate facilities-infrastructure. The research concluded that there is a need to change community behavior and work culture.